Long social distancing - Jose Maria Barrero; Nicholas Bloom; Steven J. Davis (W.E. Upjohn Institute for Employment Research, 2022)
More than ten percent of Americans with recent work experience say they will continue social distancing after the COVID-19 pandemic ends, and another 45 percent will do so in limited ways. We uncover this Long Social Distancing phenomenon in our monthly Survey of Working Arrangements and Attitudes. It is more common among older persons, women, the less educated, those who earn less, and in occupations and industries that require many face-to-face encounters. People who intend to continue social distancing have lower labor force participation-unconditionally, and conditional on demographics and other controls. Regression models that relate outcomes to intentions imply that Long Social Distancing reduced participation by 2.5 percentage points in the first half of 2022. Separate self-assessed causal effects imply a reduction of 2.0 percentage points. The impact on the earnings-weighted participation rate is smaller at about 1.4 percentage points. This drag on participation reduces potential output by nearly one percent and shrinks the college wage premium. Economic reasoning and evidence suggest that Long Social Distancing and its effects will persist for many months or years.
Keywords: E24; J21; J22; J14; D12; 330; Social distancing; infection worries; pandemic; labor force participation; potential output; college wage premium; self-assessed causal effects